Coping strategies of the local farmers in changing crop patterns of disaster prone area of Bangladesh - Uddin, Mohammad Farid (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2020.